2017
DOI: 10.1093/jpepsy/jsw101
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis: The Impact of Multicomponent Weight Management Interventions on Self-Esteem in Overweight and Obese Adolescents

Abstract: The lack of change in self-esteem suggests weight loss alone is insufficient to improve self-esteem. Multicomponent weight management interventions require a specific focus on self-esteem to improve this outcome in overweight and obese adolescents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
1
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 43 publications
2
26
1
3
Order By: Relevance
“…This view was not replicated in our review, with moderator analyses not identifying any intervention characteristics predictive of change in self‐esteem. While the review of RCTs by Murray et al reported a strong correlation between weight loss and improved self‐esteem in both intervention and control groups, the present review did not find an association. Furthermore, the current review identified that, at the latest follow‐up time point, intervention groups achieved greater improvements in self‐esteem compared with no treatment control groups, with no difference between groups for the change in weight‐related outcomes.…”
Section: Discussioncontrasting
confidence: 92%
See 4 more Smart Citations
“…This view was not replicated in our review, with moderator analyses not identifying any intervention characteristics predictive of change in self‐esteem. While the review of RCTs by Murray et al reported a strong correlation between weight loss and improved self‐esteem in both intervention and control groups, the present review did not find an association. Furthermore, the current review identified that, at the latest follow‐up time point, intervention groups achieved greater improvements in self‐esteem compared with no treatment control groups, with no difference between groups for the change in weight‐related outcomes.…”
Section: Discussioncontrasting
confidence: 92%
“…This is the first systematic review with meta‐analysis to report on the effect of obesity treatment interventions for children and adolescents with overweight or obesity on body image and extends the reviewed literature of the effect on self‐esteem.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations